Parental Education and Child Physical Health Following the BP Deepwater Horizon Oil Spill. Issue 7 (September 2022) - Stroope, Samuel; Kroeger, Rhiannon A.; Slack, Tim; Keating, Kathryn Sweet; Beedasy, Jaishree; Chandler, Thomas; Sury, Jonathan J.; Brooks, Jeremy
Purpose: To assess whether trajectories of children's physical health problems differ by parental college degree attainment in Louisiana areas highly impacted by the 2010 BP Deepwater Horizon oil spill (BP-DHOS). Design: Three waves of panel data (2014, 2016, and 2018) from the Gulf Coast Population Impact / Resilient Children, Youth, and Communities studies. Setting: BP-DHOS-impacted communities in coastal Louisiana. Participants: Parents of children aged 4-18 in a longitudinal probability sample (n = 392). Measures: Reported child physical health problems from the BP-DHOS, parental college degree attainment, and covariates. Analysis: Linear growth curve models are used to assess initial levels of and the rate of change in child physical unknown. The current study uses 3 waves physical health problems by parental college degree attainment. Explanatory variables are measured at baseline and the outcome variable is measured at all 3 waves. Results: Compared to children of parents without college degrees, children of college graduates had fewer initial health problems in 2014 (b = −.33; p = .02). Yet, this health advantage decreased over time, as indicated by their positive rate of change (b = .22; p = .01), such that the higher education health advantage was not statistically significant by 2018. Conclusion: Children of college graduates experienced a physical health advantage following the BP-DHOS, but this gap closed over time. The closure of the gap was due to the children of college graduates experiencing significant increases in reported health problems over the study period.